The importance of organizational skills: an analysis of perception of managers - Teixeira, Ana Paula Pydd (2014)
This article analyzed the content of interviews that refer to perceptions of managers with regard to the management of organizational coreÂ  competences or as leverage for competitive advantage of enterprises skills. We conducted a qualitative study that collected through in-depth interviews. A total of 14 managers were interviewed. Through the results, it was possible to identify correspondence between the perception of respondents and theÂ  available literature on the subject, stating the possible recognition of the importance of developing organizational skills.